PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR DI SMP NEGERI 4 MASAMBA - Cahyani, Apri Gita; Hasibuddin, M; Rosmiati; Mustamin; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve studen This study aims to determine the application of the Make A Match learning model and improve student learning motivation in Islamic Religious Education subject of class VIII.6 at SMP Negeri 4 Masamba, North Luwu Regency. This study is motivated by the low learning motivation of students which is indicated by a lack of attention during learning, low activeness in asking questions or discussing, and the dominant use of lecture methods which causes learning to take place monotonously. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model which consists of the planning stage, action implementation, observation, and reflection. The study was conducted in two cycles, each consisting of two meetings. The research subjects were 30 students of class VIII.6. Data collection techniques include observation, learning motivation assessment rubric, interviews, and documentation. Data analysis was carried out descriptively quantitatively and qualitatively. The results of the study indicate that the application of the Make A Match learning model is able to increase student learning motivation gradually in each cycle. The percentage of learning motivation in the pre-cycle stage was 35.09%, then increased to 57.64% in Cycle I, and again increased to 85.19% in Cycle II with a good category. In addition to increasing motivation values, students also showed positive changes in learning behavior, such as being more active in asking questions, daring to express opinions, enthusiastic about participating in learning, being able to work together in groups, and being more focused on the material being studied. The learning atmosphere became more interactive, fun, and student-centered. Based on these results, it can be concluded that the Make A Match learning model is effectively applied in Islamic Religious Education learning to increase the learning motivation of class VIII.6 students of SMP Negeri 4 Masamba, North Luwu Regency.